Emerging Roles of Liver Sinusoidal Endothelial Cells in Nonalcoholic Steatohepatitis - Kunimaro Furuta; Qianqian Guo; Petra Hirsova; Samar H. Ibrahim (Biology, 2020)
Nonalcoholic steatohepatitis (NASH) has become a growing public health problem worldwide, yet its pathophysiology remains unclear. Liver sinusoidal endothelial cells (LSEC) have unique morphology and function, and play a critical role in liver homeostasis. Emerging literature implicates LSEC in many pathological processes in the liver, including metabolic dysregulation, inflammation, angiogenesis, and carcinogenesis. In this review, we highlight the current knowledge of the role of LSEC in each of the progressive phases of NASH pathophysiology (steatosis, inflammation, fibrosis, and the development of hepatocellular carcinoma). We discuss processes that have important roles in NASH progression including the detrimental transformation of LSEC called “capillarization”, production of inflammatory and profibrogenic mediators by LSEC as well as LSEC-mediated angiogenesis. The current review has a special emphasis on LSEC adhesion molecules, and their key role in the inflammatory response in NASH. Moreover, we discuss the pathogenic role of extracellular vesicles and their bioactive cargos in liver intercellular communication, inflammation, and fibrosis. Finally, we highlight LSEC-adhesion molecules and derived bioactive product as potential therapeutic targets for human NASH.